1996
DOI: 10.1115/1.2796012
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Pulsating Flow Patterns in Curved Pipes

Abstract: The fully developed periodic laminar flow of incompressible Newtonian fluids through a pipe of circular cross section, which is coiled in a circle, was simulated numerically. The flow patterns are characterized by three parameters: the Womersley number Wo, the Dean number De, and the amplitude ratio beta. The effect of these parameters on the flow was studied in the range 2.19 < or = Wo < or = 50.00, 15.07 < or = De < or = 265.49 and 0.50 < or = beta < or = 2.00, with the curvature ratio delta fixed to be 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
3
12
0
Order By: Relevance
“…Chang & Tarbell (1985) demonstrated the existence of many multiple vortices and complex induced #ow patterns. These authors and others (Tada et al, 1996;Weston et al, 1998) showed that the direction of secondary #ow can reverse during a cycle. Bodies oscillating in a #uid may also excite steady secondary #ow components (Stuart, 1966) which Seed & Wood (1970) found to distort calibrations intended for an arterial hot-"lm probe.…”
Section: The E4ect Of Bends In Vesselsmentioning
confidence: 94%
“…Chang & Tarbell (1985) demonstrated the existence of many multiple vortices and complex induced #ow patterns. These authors and others (Tada et al, 1996;Weston et al, 1998) showed that the direction of secondary #ow can reverse during a cycle. Bodies oscillating in a #uid may also excite steady secondary #ow components (Stuart, 1966) which Seed & Wood (1970) found to distort calibrations intended for an arterial hot-"lm probe.…”
Section: The E4ect Of Bends In Vesselsmentioning
confidence: 94%
“…4(b)) to two counter-rotating vortices centered at two "focuses" at t *  0.187 (Fig. 4(d)) due to the effect of centrifugal force [1,2,6]. Terms in Fig.…”
Section: Piv Measurementsmentioning
confidence: 94%
“…Most of the results of the analytical and numerical analyses revealed interesting secondary flow in the cross section of the curved section [1][2][3][4][5][6]. Tada et al [1] studied periodic laminar flow in a curved pipe through numerical simulation, and demonstrated secondary flow evolution with increasing Womersley parameters (, square of  represents a measure of the ratio of the unsteady local acceleration to the viscous retarding force) and Dean numbers (De, represents the ratio of the centrifugal to viscous forces) [9].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations